Bridging Mayer’s cognitive theory of multimedia learning and computational thinking in tackling the cognitive load issues among young digital natives : a conceptual framework - Wan Nor Ashiqin Wan Ali; Wan Ahmad Jaafar Wan Yahaya (Penerbit Universiti Kebangsaan Malaysia, 2022)
In 2020, it is undeniable that the existence of digital natives in tertiary education is undeniable, especially in universities. They are part of a tech-savvy generation that led to technological progress that is always connected and linked based on their wishes and needs without any hesitation of time and place. They are basically using technology without guidance, but how far they can manage to handle the consequences of the technology usage and the problems that occur is always questionable. It is undeniable that a digital native must begin with at least a basic level of computer knowledge in order to manage their education and daily life. Learning about computer science not only helps students to create programs, applications or how to handle devices, but strengthens the practise of Computational Thinking (CT). CT refers to the capacity of learners to systematically tackle unstructured tasks focused on four computing concepts such as decomposition, abstraction, pattern recognition, and algorithmic thinking. The purpose of this paper is to study the relationship between CT and Mayer’s Cognitive Theory of Multimedia Learning (CTML) on the cognitive load of the learners. This research focuses on CT concepts that will be integrated with Mayer’s CTML in designing the learning material for young digital natives. Therefore, the researcher proposes a conceptual framework that aims to comprehend how to facilitate the cruciality of CT concepts in Mayer’s CTML when designing instructional learning. The proposed conceptual framework adds value in tackling the cognitive load among students, particularly in the context of the digital native generation. This paper provides several implications and highlights for further studies through a comprehensive and wide-ranging literature review.